Civic Education in United States: A Multiple Regression of Civic Education Scores from the National Assessment of Educational Progress - Bonnie L. Bittman; William B. Russell (Research in Social Sciences and Technology- OpenED Network, 2016)
Social studies teachers instruct their students through a variety of instructional pedagogies. Social science education researchers have called for K-12 teachers to transition away from a traditional lecture format and move towards a format that encourages critical thinking. Classroom debates of controversial issues are a common method by which teachers engage students in higher-order thinking. This research study utilizes the 2010 National Assessment of Educational Progress (NAEP) 12th grade civics assessment (n = 9,800) to identify instructional techniques that improve student’s score. Utilizing the NAEP Data Explorer online statistical analysis tool, a linear regression was conducted examining the effects of race, socio-economic status, instructional pedagogies, and access to newspapers and computers on student performance. Results show that discussing current events, at any frequency, increases student performance. Students who participated in classroom debates once or twice a month or less also improved. African-American and Hispanic students scored lower, as did students who qualified for free and reduced lunches. This study suggests that the inclusion of current events should be encouraged civics classes.